The Years of Jesuit Suppression, 1773-1814: Survival, Setbacks, and Transformation - Shore, Paul (Brill Research Perspectives, 2019)
The years leading up to the suppression of the Jesuits and the forty-one years, beginning in 1773, of the actual suppression, are analysed here, with special attention to individuals not usually covered in works dealing with this topic. Readership: All interested in Jesuit history, in the cultural and religious history of the late eighteenth and early nineteenth centuries.